Oleuropein from olive leaf extracts and extra-virgin olive oil provides distinctive phenolic profiles and modulation of microbiota in the large intestine. (30th June 2022) - Rocchetti, Gabriele; Luisa Callegari, Maria; Senizza, Alice; Giuberti, Gianluca; Ruzzolini, Jessica; Romani, Annalisa; Urciuoli, Silvia; Nediani, Chiara; Lucini, Luigi
Highlights: Olive leaf extracts (PLE) and extra-virgin olive oil were fermented in vitro . Oleuropein was processed into lower-molecular-weight phenolic acids. PLE and oil provided distinct impacts on faecal metabolomic profiles. Coriobacteriaceae and Lactobacillaceae were affected by PLE during fermentation. Abstract: The interest in the modulation of gut microbiota by polyphenols from olives and derived products is increasing. In this work, phenolic leaf extracts (PLE) were in vitro faecal fermented to evaluate the changes in phenolic profiles and the impact on microbiota, using a commercial extra-virgin olive oil (EVOO) as reference. The in vitro fermentation decreased oleuropein content in PLE, determining an increase of hydroxytyrosol and other phenolic metabolites. An increase (p < 0.05) of hydroxytyrosol (LogFC = 6.02; VIP score = 1.05) was also observed in fermented EVOO. Besides, PLE significantly (p < 0.05) changed amino acids (LogFC = 6.1) and fatty acids (LogFC = 5.9) profile of the faeces. Metagenomic sequencing revealed that Coriobacteriaceae at the family level, and Collinsella at the genus level, were the most affected by PLE fermentation. These findings support the modulation of the gut microbiota exerted by phenolics from PLE and EVOO.